Przestrzenie egzystencji kobiet w poezji stanu wojennego - Dąbrowska, Danuta (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Aportion of Polish culture of the nineteen-eighties, which I will provisionally term the “solidarity culture,” remains neglected by researchers. The culture of this period is usually enclosed in the history of the Polish struggle against the communist system, which is almost exclusively treated in political and sociological terms. The main issue here is its influence on the generation and sustenance of the spirit of resistance, creation of communal conscience, filling the gaps in history, and defalsifying history. These certainly are significant aspects of the solidarity movement activity in the realm of culture, but far from being the only ones. The author is interested in a narrow section of the solidarity culture referring to a specific projection of existence, that is the poetry of martial law with certain indispensable references to former periods- in particular the culture of the workers’ strikes of 1980. The researcher is mainly concerned with women’s experience and roles recorded in the poetry of martial law with respect to opposition.